Measuring surgical performance: A risky game?. Issue 4 (August 2015) - Kiernan, F.; Rahman, F.
Abstract Background Interest in performance measurement has been driven by increased demand for better indicators of hospital quality of care. This is due in part to policy makers wishing to benchmark standards of care and implement quality improvements, and also by an increased demand for transparency and accountability. Approach We describe the role of performance measurement, which is not only about quality improvement, but also serves as a guide in allocating resources within health systems, and between health, education, and social welfare systems. As hospital based healthcare is responsible for the most cost within the healthcare system, and treats the most severely ill of patients, it is no surprise that performance measurement has focused attention on hospital based care, and in particular on surgery, as an important means of improving quality and accountability. We are particularly concerned about the choice of mortality as an outcome measure in surgery, as this choice assumes that all mortality in surgery is preventable. In reality, as a low quality indicator of care it risks both gaming, and cream-skimming, unless accurate risk adjustment exists. Further concerns relate to the public reporting of this outcome measure. Conclusions As mortality rates are an imperfect measure of quality, the reputation of individual surgeons will be threatened by the public release of this data. Significant effort should be made to communicate the results to the public in an appropriate manner.